Sedimentary Indicators of Relative Sea-Level Change - Low Energy - EDWARDS, ROBIN JAMES (Elsevier, 2013)
Fine grained sediments associated with low energy conditions have proven to be useful archives of relative sea-level data. Low energy inter-tidal environments, such as saltmarshes and mangroves, are closely linked to the tidal frame. Sediments accumulating in these environments, and the plant and animal remains they contain, can therefore be used to reconstruct the former position of relative sea level in time and space. A number of methodologies employing a combined lithostratigraphic, biostratigraphic and chronostratigraphic approach have been developed to extract sea-level signals from low energy sedimentary environments. This chapter outlines these methodologies and the nature of the records they produce.
Encyclopedia of Quaternary Science (2nd Edition)
PUBLISHED
Keywords: coast; estuary; Holocene; inter-tidal; isolation basin; mangrove; relative sea-level change; saltmarsh; sea level index point; sea level indicator